Zeb1 potentiates genome‐wide gene transcription with Lef1 to promote glioblastoma cell invasion - Rosmaninho, Pedro (EMBO J, 2018)
Glioblastoma is the most common and aggressive brain tumor, with a subpopulation of stem‐like cells thought to mediate its recurring behavior and therapeutic resistance. The epithelial–mesenchymal transition (EMT) inducing factor Zeb1 was linked to tumor initiation, invasion, and resistance to therapy in glioblastoma, but how Zeb1 functions at molecular level and what genes it regulates remain poorly understood. Contrary to the common view that EMT factors act as transcriptional repressors, here we show that genome‐wide binding of Zeb1 associates with both activation and repression of gene expression in glioblastoma stem‐like cells. Transcriptional repression requires direct DNA binding of Zeb1, while indirect recruitment to regulatory regions by the Wnt pathway effector Lef1 results in gene activation, independently of Wnt signaling. Amongst glioblastoma genes activated by Zeb1 are predicted mediators of tumor cell migration and invasion, including the guanine nucleotide exchange factor Prex1, whose elevated expression is predictive of shorter glioblastoma patient survival. Prex1 promotes invasiveness of glioblastoma cells in vivo highlighting the importance of Zeb1/Lef1 gene regulatory mechanisms in gliomagenesis.